Full genome survey and dynamics of gene expression in the greater amberjack Seriola dumerili. Issue 12 (8th November 2017) - Sarropoulou, Elena; Sundaram, Arvind Y M; Kaitetzidou, Elisavet; Kotoulas, Georgios; Gilfillan, Gregor D; Papandroulakis, Nikos; Mylonas, Constantinos C; Magoulas, Antonios
Abstract: Background: Teleosts of the genus Seriola, commonly known as amberjacks, are of high commercial value in international markets due to their flesh quality and worldwide distribution. The Seriola species of interest to Mediterranean aquaculture is the greater amberjack ( Seriola dumerili ). This species holds great potential for the aquaculture industry, but in captivity, reproduction has proved to be challenging, and observed growth dysfunction hinders their domestication. Insights into molecular mechanisms may contribute to a better understanding of traits like growth and sex, but investigations to unravel the molecular background of amberjacks have begun only recently. Findings: Illumina HiSeq sequencing generated a high-coverage greater amberjack genome sequence comprising 45 909 scaffolds. Comparative mapping to the Japanese yellowtail ( Seriola quinqueriadiata ) and to the model species medaka ( Oryzias latipes ) allowed the generation of in silico groups. Additional gonad transcriptome sequencing identified sex-biased transcripts, including known sex-determining and differentiation genes. Investigation of the muscle transcriptome of slow-growing individuals showed that transcripts involved in oxygen and gas transport were differentially expressed compared with fast/normal-growing individuals. On the other hand, transcripts involved in muscle functions were found to be enriched in fast/normal-growing individuals. Conclusion: The present study provides the first insights into the molecular background of male and female amberjacks and of fast- and slow-growing fish. Therefore, valuable molecular resources have been generated in the form of a first draft genome and a reference transcriptome. Sex-biased genes, which may also have roles in sex determination or differentiation, and genes that may be responsible for slow growth are suggested.